The Most Important Axes of Future Legal Studies: The Rules of Legal Drafting - Benseddik, Fatiha; Hamli, Mohamed (Journal of Legal Studies and Researches, 2023)
Most countries are currently seeking to link university studies to the practical arena, and legal studies should not remain separate from these endeavors since the application of the law depend to a large extent on the accuracy of the drafting, the jurist must be aware of its requirements. The importance of research is evident in its most important controls.